Electric Cars For Enlightened Stars. - Voelcker, J.
This paper presents the Tesla roadster, created by a start-up, Tesla Motors. It is powered by lithium-ion batteries. It is a zero-carbon vehicle a new fashion accessory for actors like George Clooney
Keywords: Tesla Motors; Tesla roadster; Electric cars; Enlightened stars; Environment friendly sports car; Zero-carbon vehicle